The Theory of Planned Behaviour membentuk Perilaku Berwirausaha Mahasiswa - Achmad Mustofa (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
Today, the issue of demographic bonus is becoming a phenomenon in Indonesia. The impact of this phenomenon is a challenge for the government to overcome unemployment and economic growth. Open unemployment is also dominated by college graduates. The entrepreneurship course program at tertiary institutions is one of the government's efforts to educate entrepreneurial values ​​to students to answer various national economic issues. This phenomenon needs special attention and is assessed realistically. The contents of the thinking in this paper are The Theory of Planned Behavior in shaping behavior in order to grow student entrepreneurial intentions. Theory of Planned Behavior has three factors that shape entrepreneurial intentions, namely attitude toward the behavior, subjective norms, and perceived behavior control. The purpose of this study is to provide knowledge and present relevant research findings to prove the Theory of Planned Behavior's contribution to entrepreneurial intentions. The desired implication of the contents of this thought is that Theory of Planned Behavior can be applied as early as possible to students in order to support entrepreneurship courses in higher education in order to answer the challenges of national economic issues.